2019
DOI: 10.1590/s1980-220x2017042303420
|View full text |Cite
|
Sign up to set email alerts
|

Infection control and patient safety measures addressed in nursing pedagogical projects,

Abstract: Objective: To characterize teaching about patient safety and standard precautionary measures for infection prevention and control in undergraduate nursing courses. Method: A descriptive documentary analysis study carried out in undergraduate courses, with a concept equal to or greater than three in the National Student Performance Exam and in the Preliminary Course Concept, located in the state of Goiás, Brazil. Results: Six education institutions participated, with the majority being private with curricular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
7
0
8
Order By: Relevance
“…Assim sendo, foram identificados como fatores que influenciam a adesão dos profissionais às medidas de precaução padrão e de contato: a falta de conscientização, mitos e crenças por parte dos profissionais, baixa percepção de risco, descuido/esquecimento, jornadas excessivas, ritmo intenso de trabalho, falta de tempo para vestir os EPIs, ausência de recursos adequados, plantões noturnos, desgaste físico e emocional, equipes reduzidas, excesso de confiança, estresse, falta ou insuficiência de insumos, baixo compromisso da gestão hospitalar, má qualidade dos equipamentos de proteção individual, armazenamento em local distante do ponto de assistência, desconforto ao uso ou irritação cutânea, deficiente de capacitação técnica e carência de treinamentos (Porto & Marziale, 2016;Piai-Morais et al, 2015;Castro & Rodrigues, 2019;Barros et al, 2019;Boeira et al, 2019;Alvim & Gazzinelli, 2017;Moralejo et al, 2018;Ndu & Arinze-Onyia, 2017).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Assim sendo, foram identificados como fatores que influenciam a adesão dos profissionais às medidas de precaução padrão e de contato: a falta de conscientização, mitos e crenças por parte dos profissionais, baixa percepção de risco, descuido/esquecimento, jornadas excessivas, ritmo intenso de trabalho, falta de tempo para vestir os EPIs, ausência de recursos adequados, plantões noturnos, desgaste físico e emocional, equipes reduzidas, excesso de confiança, estresse, falta ou insuficiência de insumos, baixo compromisso da gestão hospitalar, má qualidade dos equipamentos de proteção individual, armazenamento em local distante do ponto de assistência, desconforto ao uso ou irritação cutânea, deficiente de capacitação técnica e carência de treinamentos (Porto & Marziale, 2016;Piai-Morais et al, 2015;Castro & Rodrigues, 2019;Barros et al, 2019;Boeira et al, 2019;Alvim & Gazzinelli, 2017;Moralejo et al, 2018;Ndu & Arinze-Onyia, 2017).…”
Section: Resultsunclassified
“…O desconhecimento dos profissionais de saúde, também é visto como um dos fatores que podem explicar os baixos índices de adesão. Estudos demonstram que esse fato pode ter correlação, tanto com a formação profissional, visto que por vezes são apontadas lacunas nos conteúdos curriculares e na prática docente, quanto com a carência de ações educativas ofertadas pelas instituições de trabalho, dificultando a construção de uma base de conhecimento sólida para a prevenção e controle de infeções (Boeira et al, 2019;Alvim & Gazzinelli, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The data showed that Patient Safety has not yet been fully incorporated into the training of nursing technicians, mainly due to the absence of the topic in the PPs and course syllabus identified in the three courses evaluated. We considered that patient safety is a transversal topic that must permeate all the training of nursing professionals (13) , and its non-approach in PPs compromises the conceptual deepening of this topic, making each discipline/teacher value only those aspects that it considers specific to the training it wants to offer (8) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fact that the topic of learning from mistakes has not been referenced by the courses cited may have outcomes in how nursing technicians perceive mistakes, analyze adverse events, and classify the types of mistakes, which may contribute to practice the punitive patient safety culture. Therefore, we must think about including this item in the training of these future professionals (13,(27)(28) .…”
Section: Discussionmentioning
confidence: 99%